Head and neck mycetoma: the mycetoma research centre experience. - Ahmed Fahal; El Sheikh Mahgoub; Ahmed Mohamed El Hassan; Angom Osman Jacoub; Doaa Hassan (Public Library of Science (PLoS), 2015)
Mycetoma is a unique neglected tropical disease which is endemic in what is known as the "mycetoma belt". The disease has many devastating impacts on patients and communities in endemic area and is characterised by massive deformity, destruction and disability. Mycetoma is commonly seen in the foot and hand and less frequent in other parts of the body. Mycetoma of the head and neck is a rarity and is associated with high morbidity and even mortality if not treated early. In this communication we report on 49 patients with head and neck mycetoma followed up at the Mycetoma Research Centre in Khartoum. Most of the reported patients had actinomycetoma and the majority were young adult males from mycetoma endemic areas in the Sudan. Most of them were students, farmers and workers. Prior to presentation the majority had long disease duration and the cause was multifactorial. Advanced disease with massive lesion, deformity and disability was the common presentation. There was no obvious history of local trauma, familial tendency or other predisposing factor identified in this group of patients. MRI and CT scan were the most accurate diagnostic tools to determine the disease extent. The treatment outcome was rather poor and characterised by low cure rate, poor outcome and high follows-up dropout. Such a gloomy outcome calls for structured and objective health education programs.